(untitled) (Bangladesh Veterinarian, 2023)
The focus of this study is to improve the pregnancy rate of cattle using different interventions with the analysis of associated risk factors. A total of 180 cows with pregnancy failure after one insemination were selected, which showed normal oestrous behaviour and vaginal mucus discharge. The animals were divided into six groups: A [control: with only Artificial Insemination (AI)]; B [penis-like device (PLD) used after AI]; C [intramuscular injection (im) of 2 ml prostaglandin-F2α at day 7 of the oestrous cycle and AI at observed oestrus], D [AI at natural oestrus followed by 2.5 ml GnRH im, repeated 4-6h after AI], group E [As group C and PLD used after AI], group F [as D and PLD used after AI]. The overall pregnancy was 55.6%. Group F had the highest pregnancy rate (70.0%). Higher pregnancy rates were in older animals of more than 4.6 years of age with parity of more than two. A significant correlation was found between age and parity; age and Artificial Insemination Technician (AIT); Body Condition Score (BCS) and breed; Reproductive Health (RH) and AIT. It is suggested that the use of hormonal treatments (with or without PLD) improved the pregnancy rate in cattle. Bangl. vet. 2022. Vol. 39, No. 1-2, 16–25